Network Pharmacology and Molecular Docking Elucidate the Pharmacological Mechanism of the OSTEOWONDER Capsule for Treating Osteoporosis - Fan, Jiashuang; Zhou, Jianli; Qu, Zhuan; Peng, Hangya; Meng, Shuhui; Peng, Yaping; Liu, Tengyan; Luo, Qiu; Dai, Lifen (Frontiers in Genetics, 2022)
Background Osteoporosis (OP) is a serious and common bone metabolic disease with bone mass lose and bone microarchitectural deterioration. OSTEOWONDER capsule is clinically used to treat OP. However, the potential regulatory mechanism of OSTEOWONDER capsule in treatment of OP remains largely unknown. Methods The bioactive compounds of herbs and their targets were identified using Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) database. The speculative targets of OP were screened out based on GeneCards, DisGeNET and Online Mendelian Inheritance in Man (OMIM) databases. The gene modules and hub genes of OP were identified using a weighted gene co-expression network analysis (WGCNA). Then, an herb-compound-target network was constructed based on above analyses.The biological function of targets was subsequently investigated and a protein-protein interaction (PPI) network was constructed to identify hub targets of OP. Finally, molecular docking was performed to explore the interaction between compounds and targets. Results A total 148 compounds of 8 herbs and corresponding 273 targets were identified based on TCMSP database. Total 4929 targets of OP were obtained based on GeneCards, DisGeNET, and OMIM databases. And six gene modules and 4235 hub genes of OP were screened out based on WGCNA. Generally, an herb-compound-target network, including 8 herbs, 84 compounds, and 58 targets, was constructed to investigate the therapeutic mechanism of OSTEOWONDER capsule for OP. The biofunction analysis indicated that 58 targets mainly associated with bone metabolism, stimulation response, and immune response. EGFR, HIF1A, MAPK8, IL6, and PPARG were identified as the hub therapeutic targets in OP. And interaction between EGFR, HIF1A, MAPK8, IL6, PPARG and corresponding compounds (quercetin and nobiletin) was performed using molecular docking. Conclusion Our finding discovered the possible therapeutic mechanisms of OSTEOWONDER capsule and supplied the potential therapeutic targets for OP.